Making a Logo as a Form of Product Identity for UMKM Menjes Kyu in Pakunden Village, Blitar - Via Aldina Auva; Rusdi Hidayat Nugroho (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
This article discusses the importance of making the logo as a form of MSME product identity. A logo is a special symbol that represents the legal property of an entity. The logo design is used as a tool to help improve community businesses, one of which is MSME. A successful logo usually reflects the characteristics of the business or organization, depicts the message to be conveyed, gives a professional and consistent impression. In many cases, the logo design process involves identification, concept development, sketching, color selection, typography and other design elements. Companies or organizations usually work with professional graphic designers to create effective and impressive logos. By creating a logo for MSMEs, it is possible for these MSMEs to be widely recognized by the public. The main purpose of having its own logo is to form an identity that differentiates it from competitors. Therefore, it is important to educate MSME actors about design using tools commonly used by printers so that the production process can be carried out easily. The resulting logo has followed the Graphic Standards Manual (GSM) rules so that it is expected to fulfill its function as a means of product and business promotion.